PRAGMATIC FUNCTION OF EMOJI AND STICKERS: ANALYSIS OF TELEGRAM CORRESPONDENCE - Rasuljonov Bexruzbek Ravshanjon o‘g‘li (TADQIQOTLAR, 2025)
ANNOTATION This article analyzes the pragmatic functions of emojis and stickers widely used in Telegram and other popular social media messengers. The study examines the role of emojis and stickers in expressing a person’s emotions in messages written through messengers and filling in communication elements that are difficult to express through written speech. In addition, the pragmatic meanings of emojis, adaptable to various situations, and the degree of their influence on the effectiveness of mutual communication, as well as the degree of their role in the development of relationships between people, are considered. According to the research results, the pragmatic features of visual symbols such as emojis and stickers in the era of modern digital technologies are highlighted.